1995
DOI: 10.1177/104973159500500106
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Making of Short- Versus Long-Term Treatment

Abstract: Practitioners'decisions of when to use ST (planned short-term) versus LT (long-term) therapy were studied via their responses to vignettes and an open-ended question about their cnteria for choosing. Using a factorial design, the effects of clients' symptoms (adjustment disorder, Dysthymic Disorder, and borderline personality disorder), gender, race (White and Black), and education (high school and college) were tested. The presence of adjustment disorder symptoms alone was able to correctly predict therapist'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…These findings indicating that practitioners in this sample did not significantly differ in their perceptions of Pat even though they detected social class differences between the two versions of the vignette were somewhat unexpected based upon prior findings regarding differences in psychotherapy utilization rates, referrals, experiences, and outcomes among individuals from non-upper middle class backgrounds (e.g., Falconnier, 2009; Nadeem et al, 2008; Rabinowitz & Lukoff, 1995; Thompson et al, 2012). However, given the relative dearth of quantitative examinations of the impacts of practitioner perceptions of client social class within psychotherapy (Goodman et al, 2012; Stabb & Riemers, 2012) and the presence of some mixed findings in previous research (e.g., Garb, 1997; Smith et al, 2011), directional hypotheses may have been somewhat premature.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…These findings indicating that practitioners in this sample did not significantly differ in their perceptions of Pat even though they detected social class differences between the two versions of the vignette were somewhat unexpected based upon prior findings regarding differences in psychotherapy utilization rates, referrals, experiences, and outcomes among individuals from non-upper middle class backgrounds (e.g., Falconnier, 2009; Nadeem et al, 2008; Rabinowitz & Lukoff, 1995; Thompson et al, 2012). However, given the relative dearth of quantitative examinations of the impacts of practitioner perceptions of client social class within psychotherapy (Goodman et al, 2012; Stabb & Riemers, 2012) and the presence of some mixed findings in previous research (e.g., Garb, 1997; Smith et al, 2011), directional hypotheses may have been somewhat premature.…”
Section: Discussionmentioning
confidence: 43%
“…For example, findings have demonstrated that clients from lower class backgrounds are less likely to be referred to therapy that is insight-oriented rather than supportive in comparison to their peers from more middle and upper class backgrounds (e.g., Franklin, 1985; Levy & Kahn, 1970; Neumann, Salganik, Rabinowitz, Bauer, & Kastner, 1990; Rabinowtiz & Lukoff, 1995). Research also has indicated that psychotherapy clients from lower social class backgrounds are less likely to access mental health care given a myriad of barriers (e.g., Nadeem, Lange, & Miranda, 2008) and that they have higher rates of discontinuing therapy (e.g., Miranda, Azocar, Komaromy, & Golding, 1998; Siefert, Heflin, Corcoran, & Williams, 2000) in comparison to clients from more upper class backgrounds.…”
Section: Social Class and Psychotherapymentioning
confidence: 99%
“…Similarly, prognostic ratings did not vary as a function of social class when clinicians interviewed actors who portrayed clients (Wright & Hutton, 1977). In other studies, less favorable prognostic ratings were made for lower‐class clients than for middle‐class or upper‐class clients when clinicians were given case histories (Franklin, 1985; Rabinowitz & Lukoff, 1995; Sutton & Kessler, 1986), when they listened to a recording of an intake interview (Lee & Temerlin, 1970), and when they were given Rorschach test results (Haase, 1964; Levy & Kahn, 1970; Trachtman, 1971).…”
Section: Social Class Biasmentioning
confidence: 98%
“…In all of the studies, different groups of clinicians were given different case histories that were identical except for the designation of race, or they watched videotapes of actors portraying clients and the videotapes were identical except for the race of the actors. When prognostic ratings made by White and Black clinicians were pooled together, prognoses were more favorable for Black clients than for White clients in three studies (Lewis et ah, 1990; Schwartz & Abramow‐itz, 1975; Strickland et al, 1988) and equally favorable for Black clients and White clients in one study (Rabi‐nowitz & Lukoff, 1995). When ratings were analyzed separately for White and Black clinicians, prognoses made by White clinicians were unaffected by client race (Bloch et al, 1980; Franklin, 1985), but Black clinicians tended to make prognoses that were more favorable for Black clients than White clients (Benefee et al, 1976; Franklin, 1985).…”
Section: Race Biasmentioning
confidence: 99%
See 1 more Smart Citation